2022
DOI: 10.24234/se.v5i1.288
|View full text |Cite
|
Sign up to set email alerts
|

How Visually Impaired Learners Construct Opportunities to Learn Mathematics?

Abstract: Many studies view inclusive education practices as having the potential to improve equal access to education, where the existing barriers are reduced. In mathematics specifically, it is believed that providing more opportunities to learn for learners with special educational needs can improve their performance and result in scaling down the mathematics achievement gap. A differing perspective from recent empirical research that focused on mathematics instruction involving learners with special educational need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Research further shows that among the other irking factors that put CwPDs at risk of absconding from school include lack of funding which leads to a shortage of teaching and learning materials, overcrowded classrooms (Mohale, 2020;Mosia, 2017) and unqualified teachers that comprise of an inclusive curriculum (Makwembere, 2021;Matobako, 2021). In concurrence with the above authors, Makuyana (2022) explained that mainstream schools do not have enough resource support for disabled learners; this leaves parents with no option but to withdraw their children from school.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Research further shows that among the other irking factors that put CwPDs at risk of absconding from school include lack of funding which leads to a shortage of teaching and learning materials, overcrowded classrooms (Mohale, 2020;Mosia, 2017) and unqualified teachers that comprise of an inclusive curriculum (Makwembere, 2021;Matobako, 2021). In concurrence with the above authors, Makuyana (2022) explained that mainstream schools do not have enough resource support for disabled learners; this leaves parents with no option but to withdraw their children from school.…”
Section: Literature Reviewmentioning
confidence: 97%
“…"…effective communication and collaboration is needed to address the challenges in the schools." Some authors suggest that effective communication among school board members is essential as it involves goal-setting, problem-solving and decision-making (Harris, 2014;Matobako, 2021;Padayachee, 2021;Vatrella, 2015). Nevertheless, the study by Kheswa (2017) revealed that working with authoritarian principals is a major debilitating factor because there is no effective communication.…”
Section: Lack Of Support From the Department Of Education In Finding ...mentioning
confidence: 99%